Act of Feb. 16, 1875, 1874-75 Ark. Acts 156, § 1 - (:unkn) unknown (General Publisher, 1875)
Prohibited the carrying in public of any “pistol, gun, knife, dirk, bludgeon, or other offensive weapon, with intent to assault any person.” Punishable by a fine of $25-100.
--
Keywords: CARRY - INTENT TO COMMIT CRIME